The Value of Static Perimetry in the Diagnosis and Follow-up of Negative Dysphotopsia. Issue 8 (23rd August 2022) - Rozendal, Lisa R. W.; van Vught, Luc; Luyten, Gregorius P. M.; Beenakker, Jan-Willem M.
Abstract : SIGNIFICANCE: There is a clinical need for a quantitative test to objectively diagnose negative dysphotopsia, especially because the diagnosis is generally assessed using patients' subjective descriptions. In the search of a clinical test to objectify the shadow experienced in negative dysphotopsia, this study excludes static perimetry as suitable evaluation method. PURPOSE: This study aimed to evaluate the value of static perimetry in the objective assessment and follow-up of negative dysphotopsia. METHODS: Peripheral 60-4 full-threshold visual field tests were performed in 27 patients with negative dysphotopsia and 33 pseudophakic controls. In addition, 11 patients with negative dysphotopsia repeated the test after an intraocular lens exchange. Both the total peripheral visual field and the averaged peripheral visual field from 50 to 60° eccentricity were compared between patients and controls, and pre-operatively and post-operatively in patients who had an intraocular lens exchange. RESULTS: The peripheral visual fields from 30 to 60° did not show significant differences between patients with negative dysphotopsia and pseudophakic controls. Analysis of the peripheral visual field from 50 to 60° showed a median [Q1, Q3] of 20.0 [17.1, 22.5] dB in the negative dysphotopsia group compared with 20.1 [15.5, 21.3] dB in the control group ( P = .43). Although 82% of patients treated with an intraocular lens exchange subjectively reported improvement of their negative dysphotopsia complaints post-operatively, there were no significant differences in their total peripheral visual field or averaged peripheral visual field from 50 to 60° ( P = .92). CONCLUSIONS: Full-threshold static perimetry with a Goldmann size III stimulus up to 60° eccentricity does not show significant differences between patients with negative dysphotopsia and pseudophakic controls or between measurements before and after intraocular lens exchange. Therefore, this type of static perimetry cannot be used as a quantitative objective test for diagnosis or follow-up of patients with negative dysphotopsia.